Winter is (not) coming: Acoustic monitoring and temperature variation across important bat hibernacula - Nia Toshkova; Maksim Kolev; Stanimira Deleva; Tzvetan Simeonov; Vasil Popov (Biodiversity Data Journal)
Little is known about the winter bat activity in Bulgaria, which poses challenges in monitoring potential deviations in their behaviour as a consequence of the warming climate. Using passive acoustic monitoring, we investigated the winter activity in some of Europe’s largest hibernacula. Our findings reveal cave and species-specific activity patterns. Activity was observed throughout each month of the survey, with distinct peaks on specific days. At one high-elevation site, bat activity was restricted to a single night, while the highest overall activity occurred at the highest elevation site (1325 m). The most active species was Myotis capaccinii (Bonaparte, 1837). While bats were mostly active right after sunset following their usual circadian rhythm, some daytime activity was also observed, including emergence at temperatures as low as -8°C. At sites with sufficient activity data, external temperature emerged as a significant positive predictor of bat activity, with higher temperatures associated with increased activity. Our data also suggest that bats rarely forage near the roost entrances. The observed variability in activity levels between study sites highlights the need for high-resolution, site-specific data rather than broad generalisations.